2013
DOI: 10.1063/1.4822300
|View full text |Cite
|
Sign up to set email alerts
|

Formation of highly oriented nanopores via crystallization of amorphous Nb2O5 and Ta2O5

Abstract: Formation of self-oriented and -elongated nanopores in annealed amorphous Nb 2 O 5 and Ta 2 O 5 was analyzed by transmission electron microscopy. Along with their crystal growth, nanopores were spontaneously elongated in the a-axis direction perpendicular to the longitudinal b axis of the orthorhombic structures with strong anisotropy. In addition, the effect of tungsten on the nanovoid formation in annealed amorphous Nb 2 O 5 and Ta 2 O 5 was also studied. Additive tungsten atoms of a few atomic percent into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We confirmed that the locations of the peaks and shoulders remain unchanged regardless of Q max , suggesting that the peaks and shoulders discussed here are not ghost but real ones. These peaks are in good agreement with the bond lengths of Ta-O, O-O, Ta-Ta (1), and Ta-Ta (2), respectively (the number in the parenthesis indicates the shorter and longer distance), in a-Ta 2 O 5 [21,25]. Therefore, the atomic distribution in a-Ta 2 O 6.6 S 0.7 prepared via anodization is essentially similar to that in a- Ta differs clearly from that of the as-anodized one.…”
Section: (A) For Comparison G(r) Of In Amorphous Ta 2 O 5 (A-ta 2 Osupporting
confidence: 72%
See 2 more Smart Citations
“…We confirmed that the locations of the peaks and shoulders remain unchanged regardless of Q max , suggesting that the peaks and shoulders discussed here are not ghost but real ones. These peaks are in good agreement with the bond lengths of Ta-O, O-O, Ta-Ta (1), and Ta-Ta (2), respectively (the number in the parenthesis indicates the shorter and longer distance), in a-Ta 2 O 5 [21,25]. Therefore, the atomic distribution in a-Ta 2 O 6.6 S 0.7 prepared via anodization is essentially similar to that in a- Ta differs clearly from that of the as-anodized one.…”
Section: (A) For Comparison G(r) Of In Amorphous Ta 2 O 5 (A-ta 2 Osupporting
confidence: 72%
“…The experimental details for sputtered samples are in Ref. [16,21]. g(r) of annealed a-Ta 2 O 5 is an original data for this publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural analysis Figure 1 shows cross-sectional TEM images and the corresponding SAED for 100 nm-thick specimens of amorphous 30 The structures of the specimens were confirmed to remain amorphous after annealing at the conditions. Therefore, the upper limit temperature for diffusionannealing experiments was considered to be these temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the density functional theory, it has been reported that vacancies are preferentially trapped with Sn atoms in Ge. [20][21][22][23] In general, amorphous materials contain free volumes, [24][25][26] which presumably causes the Sn-vacancy pairs. As a consequence, substitutional Sn atoms, with a concentration that is much higher than the solubility limit, are stabilized in the crystalline Ge matrix.…”
Section: B Compositional Changes During Thermal Annealingmentioning
confidence: 99%